1999
DOI: 10.1111/j.1151-2916.1999.tb01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Phase Diagram Study and Thermodynamic Optimization of the Ag‐Bi‐O System

Abstract: 2 by DTA. There are no ternary phases stable at ambient pressure. Presently measured transformation temperatures have been combined with existing oxygen activity measurements in the metal liquid to optimize thermodynamic parameters describing the liquid phase. The resulting fit is excellent. EDX measurements of the composition in the oxide liquid have a rather low precision but confirm the thermodynamic optimization. However, some uncertainties remain concerning the liquid composition at the eutectic transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The selected activity coefficients are compiled in Table 2. With these parameters, the following major properties of the systems are well reproduced at 1000 C: Ag solubility of about 5 wt.% both in PbO (Shao et al, 1993) and in Bi 2 O 3 (Assal et al, 1999) in air, full miscibility of Bi 2 O 3 and PbO (Diop et al, 2009), distribution ratio of Ag in PbePbO (Ueda et al, 2005), distributions ratio of Sn, Sb and Bi between AgePb alloy and PbO (Ueda et al, 2009).…”
Section: Thermodynamic Modelling Of Cupellationmentioning
confidence: 80%
“…The selected activity coefficients are compiled in Table 2. With these parameters, the following major properties of the systems are well reproduced at 1000 C: Ag solubility of about 5 wt.% both in PbO (Shao et al, 1993) and in Bi 2 O 3 (Assal et al, 1999) in air, full miscibility of Bi 2 O 3 and PbO (Diop et al, 2009), distribution ratio of Ag in PbePbO (Ueda et al, 2005), distributions ratio of Sn, Sb and Bi between AgePb alloy and PbO (Ueda et al, 2009).…”
Section: Thermodynamic Modelling Of Cupellationmentioning
confidence: 80%
“…1. From the phase diagram of Bi 2 O 3 -Ag [35], if the composition is shifted from the eutectic point to a higher abundance of Bi 2 O 3 , it is the Bi 2 O 3 phase that should crystallize first in contact with a liquid phase. While, if the composition is shifted toward a higher abundance of Ag, the Ag phase should crystallize first, and then, the eutectic will be made of Bi 2 O 3 and Ag.…”
Section: Resultsmentioning
confidence: 99%
“…From the Ag-(Bi 2 O 3 ) phase diagram [35] in the mentioned system, several transformations at an oxygen partial pressure of 1.01 9 10 5 Pa are observed To investigate the phase in which silver is placed in the Bi 2 O 3 -Ag composite during growth and to understand the processes which lead to the formation of silver nanoparticles after the annealing of the material, high-resolution transmission electron microscopy has been performed on the as-grown and annealed-in-vacuum samples. Both the selected area electron diffraction and the energy-dispersive X-ray spectroscopy confirmed that the as-grown material consists of two phases.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal Growth : According to the phase diagram of Assal et al [ 34 ] the Ag-1 / 2 (Bi 2 O 3 ) system undergoes following transformations: eutectic, monotectic, and allotropic of Bi 2 O 3 ( Figure 8 ). At an oxygen partial pressure of 1.01 × 10 5 Pa, a monotectic reaction (Ag) + Liq2↔Liq1 occurs at 939 °C, while a eutectic reaction (Ag) + α-Bi 2 O 3 ↔ Liq2 occurs at 687 °C with a eutectic composition of 18.54 mol% Ag and 81.46 mol% Bi 2 O 3 .…”
Section: Methodsmentioning
confidence: 99%
“…We obtained Bi 2 O 3 -Ag as one of the few available eutectic compositions that includes metallic silver, with a composition of 84.5 mol% Bi 2 O 3 and 15.4 mol% Ag. [ 34 ] The micro-pulling-down method [ 35,36 ] was used for fabrication. This technique has previously been successfully applied for the directional growth of crystalline fi bers, [ 37 ] eutectics, [ 38,39 ] and nanoplasmonic materials based on glasses doped with nanoparticles.…”
Section: D Multiscale Metallodielectric Compositementioning
confidence: 99%